Time discounting predicts loan forbearance takeup - Edina Berlinger; Sára Khayouti; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
During the COVID-19 pandemic, many countries eased the burden of borrowers through loan forbearance. Using a representative sample of the Hungarian adult population, we investigate if time discounting and locus of control predict who takes up loan forbearance. We find convincing evidence that time discouting associates with the resort to forbearance: individuals who discount the future less are less likely to take up forbearance, even if we take into account their educational level and financial status. Data suggest that the channel through which time discounting and loan forbearance are related is savings. There is no statistically significant relationship between locus of control and forbearance takeup.
Keywords: G41; G51; 330; loan forbearance; locus of control; time discounting